PERAN KOPERASI SIMPAN PINJAM CREDIT UNION PANCUR DANGERI TERHADAP KESEJAHTERAAN ANGGOTA DI KECAMATAN SIMPANG DUA KABUPATEN KETAPANG KALIMANTAN BARAT - Yunita Nining (Fakultas Pertanian UST, 2023)
This research aims to determine the role of credit union savings and loans cooperatives on the welfare of members in Simpang Dua District, Ketapang Regency, West Kalimantan. The basic method in this study is the quantitative descriptive research method. The sampling technique uses purposive sampling technique. Data retrieval technique using questionnaires. Determination of the number of samples using the slovin formula and the size of the sample of 100 respondents. The data analysis method in this study uses multiple linear regression analysis with partial significance test (t test), and test determination test (R2). The results showed that: 1. There is no effect of providing capital on the welfare of members (influence with sig = 0.348<0.05), 2. There is a significant effect of service quality on member welfare (with sig= 0.013<0.05), 3. There is an effect of the loan interest rate on the welfare of members (with sig=0.000<0.05), 4. The provision of capital, quality of service, and interest rate on loans simultaneously affect the welfare of members (influence with sig=0,000<0,05).